Respuesta :

Answer:

Step-by-step explanation:

We will make a substitution to make our work easier (when we get there).  We also need to know that

[tex]i^2=-1[/tex]

We will use that as another substitution.  First, let's make the job of factoring a bit easier.  Here's the first substitution.  We will let

[tex]x^4=u^2[/tex]

Therefore,

[tex]x^2=u[/tex]

Now we will write the polynomial in terms of u instead of x:

[tex]f(x)=u^2+21u-100[/tex]

Solve for the values of u by setting the polynomial equal to 0 and factoring.  When you factor, you will get:

[tex](u+25)(u-4)[/tex]

But don't forget that

[tex]x^2=u[/tex]

so we have to put those back in now:

[tex](x^2+25)(x^2-4)=0[/tex]

By the Zero Product Property, either

[tex]x^2+25=0[/tex] or

[tex]x^2-4=0[/tex]

We will factor the first term.  Solving for x-squared gives us:

[tex]x^2=-25[/tex] and

x = ±√-25

which simplifies down to

x = ±√-1 × 25

we can sub in an i-squared for the -1:

x = ±√[tex]i^2*25[/tex]

The square root of i-squared is "i" and the square root of 25 is 5, so

x = ±5i

The next one is a bit easier.  If

[tex]x^2=4[/tex], then

x = ±2

You can see you have 4 solutions.  But you knew that already, since this is a 4th degree polynomial.  The types of solutions are:  2 real, 2 imaginary